Lactate peak in youth swimmers: Quantity and time interval for measurement after 50-1500 maximal efforts in front crawl - Zacca, R.; Lopes, A. L.; Teixeira, B. C.; da Silva, L. M.; de Matos, C. C.; de Souza Castro, F. A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
The aim of this study was to compare lactate peak and area under the curve lactate-time (AUC) values at 50, 100, 200, 400, 800 and 1500 m maximal efforts in youth swimmers performing front crawl. Twelve {eight males and four females) youth swimmers {15.6 ± 0.9 years old, 63.0 ± 7.2 kg body mass, 1.75 ± 0.08 m height, and 1.81 ± 0.10 m arm span) volunteered to participate in this study. The protocol involved the performance in a randomised order of 50, 100, 200, 400, 800, and 1500 m allout effort (24h interval). Capillary blood samples (~25 ~I) for blood lactate concentration ((La]) analysis were collected after 10 min rest (Rest), after warm-up (Pre) and during the recovery period (1, 3, 5 and 7 min, [La]peakl after each event (50-1500 m) using Accutrend Plus (Roche®). AUC of [La] was calculated by the trapezoidal mathematical method, i.e., the sum of trapezoid areas AUC of [La] was expressed as percentage difference between each distance, with 50 being 100%. The highest [La] observed in 100 and 200 m indicates the high glycolitic contribution between 50-1500 events. Factorial AN OVA found no difference between [La]peak of 100 and 200 m, but AUC showed difference of+ 3% between 100 and 200m. Area under the curve (AUC) of [La] may be applied in swimming.